Mariusz Wilk`s tropa – from Solidarity to by Oniego house - Kajstura, Justyna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The subject of this article is an analysis of the extraordinary path of life of the Polish writer Mariusz Wilk, visualizing in the pages of his journals. The author as a young man was Lech Walesa’s press spokesman, and then life choices led him to the Far North, where he lived in harsh conditions far from another people settlements. Subject of the analysis are the latest books in the quartet, entitled `North journal`. Reading the autobiographical plots included in the North Quartet has given a broader perspective on the facts, opinions, events and socio-cultural processes of the last two decades. Moreover genre peculiarity of the journal, admittedly considered to be non-fiction, has been the reason for reflection on the temptation of author`s autocreation. The article also analyzes the tensions arising from the penetration of biographies of authors read and authors analyzed by Wilk as well as his actual (real) and created biography.